2020
DOI: 10.1016/s2214-109x(20)30221-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of childhood smoking and adult mortality: prospective study of 120 000 Cuban adults

Abstract: BackgroundThe average age at which people start smoking has been decreasing in many countries, but insufficient evidence exists on the adult hazards of having started smoking in childhood and, especially, in early childhood. We aimed to investigate the association between smoking habits (focusing on the age when smokers started) and causespecific premature mortality in a cohort of adults in Cuba.Methods For this prospective study, adults were recruited from five provinces in Cuba. Participants were interviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
0
29
0
2
Order By: Relevance
“…Third, this cohort of VIPs was not designed to evaluate gender-related differences and, therefore, this analysis remains of retrospective and thesis-generating character per se. Fourth, other potential confounders, such as smoking status or socioeconomic data are lacking, which is another limitation 27 . Fifth, we observed a sex-specific difference in 30-day-mortality, but not in ICU mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this cohort of VIPs was not designed to evaluate gender-related differences and, therefore, this analysis remains of retrospective and thesis-generating character per se. Fourth, other potential confounders, such as smoking status or socioeconomic data are lacking, which is another limitation 27 . Fifth, we observed a sex-specific difference in 30-day-mortality, but not in ICU mortality.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Other major studies have reported on the prevalence of tobacco use in India, China, the Asia-Pacific region, Mexico, Cuba, and Russia. [36][37][38][39][40][41][42] Tobacco provides no physiological or pharmacological benefit to users. It has been estimated that there are approximately 1.3 billion smokers worldwide, 82% of whom are from middle-and low-income countries.…”
Section: Tobacco Smokingmentioning
confidence: 99%
“…Tobacco use among youth increases the risk of reduced lung function, impaired lung growth, and early onset of chronic respiratory disease [ 11 ]. Starting to smoke in childhood doubles the risk of premature death [ 12 ]. The lungs continue to grow well into adulthood, but inhaling the toxic substances of tobacco smoke slows this process and causes potentially irreversible lung damage [ 11 ].…”
mentioning
confidence: 99%